A prospective study of respiratory symptoms associated with chronic arsenic exposure in Bangladesh: findings from the Health Effects of Arsenic Longitudinal Study (HEALS). Issue 6 (3rd June 2010) - Parvez, Faruque; Chen, Yu; Brandt-Rauf, Paul W; Slavkovich, Vesna; Islam, Tariqul; Ahmed, Alauddin; Argos, Maria; Hassan, Rabiul; Yunus, Mahbub; Haque, Syed E; Balac, Olgica; Graziano, Joseph H; et al.
Abstract : Background and aims: A prospective cohort study was conducted to evaluate the effect of arsenic (As) exposure from drinking water on respiratory symptoms using data from the Health Effects of Arsenic Exposure Longitudinal Study (HEALS), a large prospective cohort study established in Ariahazar, Bangladesh in 2000–2002. A total of 7.31, 9.95 and 2.03% of the 11 746 participants completing 4 years of active follow-up reported having a chronic cough, breathing problem or blood in their sputum, respectively, as assessed by trained physicians. Methods: Cox regression models were used to estimate HRs for respiratory symptoms during the follow-up period in relation to levels of chronic As exposure assessed at baseline, adjusting for age, gender, smoking, body mass index, education and arsenic-related skin lesion status. Results: Significant positive associations were found between As exposure and respiratory symptoms. As compared with those with the lowest quintile of water As level (≤7 μg/l), the HRs for having respiratory symptoms were 1.27 (95% CI 1.09 to 1.48), 1.39 (95% CI 1.19 to 1.63), 1.43 (95% CI 1.23 to 1.68) and 1.43 (95% CI 1.22 to 1.68) for the second to fifth quintiles of baseline water As concentrations (7–40, 40–90, 90–178 and >178 μg/l), respectively. Similarly, the corresponding HRs in relation to the second to fifth quintiles of urinary arsenic were 1.10 (95% CI 0.94 to 1.27), 1.11 (95% CI 0.95 to 1.29), 1.29 (95% CI 1.11 to 1.49) and 1.35 (95% CI 1.16 to 1.56), respectively. These associations did not differ appreciably by cigarette smoking status. Conclusions: This prospective cohort study found a dose–response relationship between As exposure and clinical symptoms of respiratory diseases in Bangladesh. In particular, these adverse respiratory effects of As were clearly evident in the low to moderate dose range, suggesting that a large proportion of the country's population may be at risk of developing serious lung diseases in the future.